An Integrative Approach to Improve Students' Cognitive Ability Through Online Learning in The Covid-19 Pandemic - Demina Demina; David David; Nadia Nadia; Oktri Permata Lani; Fatkuroji Fatkuroji (Ta'dib, 2022)
This research has revealed the decline in students' cognitive abilities in online learning during the Covid-19 pandemic. The decline in students' cognitive abilities in studying independently at home by completing various tasks without classmates. This study aims to determine how integrated learning can improve students' cognitive abilities happened in learning the Qur'an and hadith. The research method with an experimental quantitative approach was carried out to measure students' cognitive abilities through integrated learning, in the class XI State Madrasah Aliyah Padang Japang Payakumbuh student group with a research sample of 17. The experimental group was treated with the connected type of integrated learning treated The research applied pre-test post-test control group design. Before the treatment of the sample group, a pre-test was carried out, and after the learning was carried out a post-test. The results showed that there was a significant increase in students' cognitive knowledge through connected type of integrated learning in learning the Qur'an Hadith of Madrasah Aliyah Negeri Padang Japang Payakumbuh with an average pretest score of 32.17 and an average post-test score of 48.47. Thus, improving students' cognitive abilities can be done through integrated learning.